Khazanah Ekoleksikon ‘Green’ di Green School Bali - Ni Putu Tirka Widanti (Universitas Udayana, 2022)
The diversity of the language of the environment of Green School Bali needs to be studied, especially the treasury of green ecolexicon as they reflect strategical effort to preserve local wisdom of Balinese culture. This study used a descriptive qualitative approach. Data was obtained from the Green School Bali educational environment by using observation and interviews method. The results shown that the grammatical category of the ‘green’ lexicon is in the form of nouns and verbs that are in the form of basic words and phrases and the ‘green’ syntactic construction at Green School Bali contains these natural lexicons, including noun phrases such as bambu hitam ‘black bamboo’, and verb phrases such as bermain Jegog ‘play Jegog’ while the social praxis dimension of the green ecolexicon namely the ideological dimension, the sociological dimension and the biological dimension. This research also uniquely contributes to preserving the concept of local wisdom in real action in the context of international education in Bali.